Identification of a novel strong promoter from the anhydrobiotic midge, Polypedilum vanderplanki, with conserved function in various insect cell lines - Miyata, Yugo (Sci Rep, 2019)
Larvae of the African midge Polypedilum vanderplanki (Diptera: Chironomidae) show a form of extreme desiccation tolerance known as anhydrobiosis. The cell line Pv11 was recently established from the species, and these cells can also survive under desiccated conditions, and proliferate normally after rehydration. Here we report the identification of a new promoter, 121, which has strong constitutive transcriptional activity in Pv11 cells and promotes effective expression of exogenous genes. Using a luciferase reporter assay, this strong transcriptional activity was shown to be conserved in cell lines from various insect species, including S2 (Drosophila melanogaster, Diptera), SaPe-4 (Sarcophaga peregrina, Diptera), Sf9 (Spodoptera frugiperda, Lepidoptera) and Tc81 (Tribolium castaneum, Coleoptera) cells. In conjunction with an appropriate selection maker gene, the 121 promoter was able to confer zeocin resistance on SaPe-4 cells and allowed the establishment of stable SaPe-4 cell lines expressing the fluorescent protein AcGFP1; this is the first report of heterologous gene expression in this cell line. These results show the 121 promoter to be a versatile tool for exogenous gene expression in a wide range of insect cell lines, particularly useful to those from non-model insect species.